Stoker se denke aangaande die reg en geregtigheid - Vyver, J. D. van der (Koers, 1994)
Stoker was already of pensionable age when he first developed an interest in the problems o f jurisprudence, although he had no academic training in the discipline o f law. For that reason, his exposition o f jurisprudential notions and ideas in many respects lacks a proper understanding of the exact components o f legal concepts and distinctions familiar to the legally trained mind. The general exposition to be found in his philosophy pertaining to the law, human rights and the legal order nevertheless reflects amazing insights and original thought. The main thrust o f his jurisprudence remained focused upon uncovering the essential nature of the juridical aspect of reality, which he defined as "service in office" ("ampsbediening "): Every human person has a particular calling in life and is required by God to fulfil that calling. The ontic law (the ‘real law' as it would have been had there been no sin) lays down the conditions that would make it possible for a person to accomplish her earthly avocation. An internal analysis would expose distinct 'cosmic dimensions’ of the law, human rights and the legal order. The juridical aspect per se constitutes aparticular modality of individual and social ideostantic ‘things’; its dynamic aspect may be uncovered by perceiving the law from the perspective of the cosmic dimension o f occurrences; and its elements of ‘good’ and 'bad' will be brought to light by analysing the law, human rights and the legal order with a view to the cosmic dimension of values. Stoker’s perception of the ontic law is comparable to the notion of natural law - redesigned by Stoker, though, from a decidedly Christian perspective.